2021
DOI: 10.1007/s10531-021-02141-7
|View full text |Cite
|
Sign up to set email alerts
|

Elephant rewilding indirectly affects the abundance of an arboreal but not generalist savanna lizard

Abstract: This is the submitted manuscript (pre-print version) of the article.This is the version that represents the main opportunity for researchers to get input with regard to corrections and additions, before the peer-review process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…While the exact consequences of the prehistoric and historic megafauna range contractions and extinctions for vegetation structure and ecosystem function are poorly known, several studies point to widespread major effects: South American savannas are estimated to have been much more open, like the African savannas (Doughty, Faurby, & Svenning, 2016a), Great Britain had more open vegetation in the Last Interglacial than in the Early Holocene (Sandom, Ejrnaes, et al, 2014b), grassy ecosystem fire activity increased with grazer extinction severity globally (Karp et al, 2021), megafauna extinction in northern Australia led to increased wildfires and a subsequent shift from mixed savanna to fire-tolerant sclerophyll vegetation (Rule et al, 2012), and vegetation changes have been coupled with megafauna losses in North America (Gill et al, 2009). Furthermore, large and cascading ecosystem effects of large herbivores are also evident in the few areas where well-developed wild herbivore faunas still exist (Ripple et al, 2015), for example extirpation of large herbivores in Mozambique led to an expansion in the alien woody species Mimosa pigra and herbivore reintroductions decreased it back to pre-extirpation levels (Guyton et al, 2020), the re-establishment of bison numbers in Yellowstone National Park is limiting woody plant density (Beschta et al, 2020), long-term elephant impact in African savannas decreases tree density (Gordon et al, 2021) and vegetation height (Davies et al, 2018) while increasing vegetation height variability (Davies et al, 2018), and exclosure experiments in temperate forests have shown that saplings have a hard time escaping the pressure from large herbivores under closed forest canopy as well as in canopy gaps (Churski et al, 2017). From this body of knowledge, it is obvious that large herbivores play a major role in shaping ecosystem structure and functions, with important implications for ecosystem restoration (Donlan et al, 2006;Ripple et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While the exact consequences of the prehistoric and historic megafauna range contractions and extinctions for vegetation structure and ecosystem function are poorly known, several studies point to widespread major effects: South American savannas are estimated to have been much more open, like the African savannas (Doughty, Faurby, & Svenning, 2016a), Great Britain had more open vegetation in the Last Interglacial than in the Early Holocene (Sandom, Ejrnaes, et al, 2014b), grassy ecosystem fire activity increased with grazer extinction severity globally (Karp et al, 2021), megafauna extinction in northern Australia led to increased wildfires and a subsequent shift from mixed savanna to fire-tolerant sclerophyll vegetation (Rule et al, 2012), and vegetation changes have been coupled with megafauna losses in North America (Gill et al, 2009). Furthermore, large and cascading ecosystem effects of large herbivores are also evident in the few areas where well-developed wild herbivore faunas still exist (Ripple et al, 2015), for example extirpation of large herbivores in Mozambique led to an expansion in the alien woody species Mimosa pigra and herbivore reintroductions decreased it back to pre-extirpation levels (Guyton et al, 2020), the re-establishment of bison numbers in Yellowstone National Park is limiting woody plant density (Beschta et al, 2020), long-term elephant impact in African savannas decreases tree density (Gordon et al, 2021) and vegetation height (Davies et al, 2018) while increasing vegetation height variability (Davies et al, 2018), and exclosure experiments in temperate forests have shown that saplings have a hard time escaping the pressure from large herbivores under closed forest canopy as well as in canopy gaps (Churski et al, 2017). From this body of knowledge, it is obvious that large herbivores play a major role in shaping ecosystem structure and functions, with important implications for ecosystem restoration (Donlan et al, 2006;Ripple et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the broader habitat preferences discussed earlier, elephants may additionally impact fauna at finer scales by moderating habitat quality and/or predation risk (Gordon et al, 2021). Our cross‐reserve comparisons showed that larger coarse woody debris items were more common at younger than older reintroduction times.…”
Section: Discussionmentioning
confidence: 99%
“…The following attributes were also noted for each tree: perpendicular distance from transect, the presence of at least one primary stem broken at the tree trunk, and the presence of small (2–5 cm minimum entry width), medium‐sized (>5–10 cm minimum entry width), and large (>10 cm minimum entry width) tree hollows (Gibbons et al, 2002). The density of trees and hollow bearing trees were assessed at each site using the methods described in what follows and in Gordon et al (2021). The percentage of trees with at least one primary stem broken was calculated at each site as a measure of elephant‐mediated tree impact.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Megafauna includes mammals that weigh >45 kg and can have an important ecological role in shaping habitats and entire ecosystems (Martin and Klein, 1984;Mills et al, 1993;Gill et al, 2009). Megafauna can modify vegetation composition (Gordon et al, 2021), influence seed dispersal (Peres et al, 2016), maintain grass versus woody cover (Sankaran et al, 2005), change soil carbon storage (Derner et al, 2006;Wigley et al, 2020) and suppress fire activity (Waldram et al, 2008). In modern savannas, antelope-induced grazing suppresses grass and tree growth (Staver and Bond, 2014) while rhinos can limit fire activity by feeding on grasses and controlling fuel build up (Waldram et al, 2008).…”
Section: Introductionmentioning
confidence: 99%